2018
DOI: 10.1111/bph.14440
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric and orthosteric pharmacology of cannabidiol and cannabidiol‐dimethylheptyl at the type 1 and type 2 cannabinoid receptors

Abstract: The pharmacological activity of CBD and CBD-DMH in HEK293A cells and their modelled binding sites at CB and CB receptors may explain their in vivo effects and illuminates the difficulties associated with the development of allosteric modulators for CB and CB receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
184
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(194 citation statements)
references
References 59 publications
(112 reference statements)
2
184
0
8
Order By: Relevance
“…CBD has a low affinity for the CB1 receptor and functions as a noncompetitive allosteric antagonist. 23,38,39 When used at up to 5 lM, CBD fully inhibited the 2-LG re-sponse and substantially inhibited (*70%) the ACEA and AEA responses. However, its effect on 2-AG at this concentration was less pronounced, but others have also showed that it does not fully inhibit maximal 2-AG responses at this concentration in a similar b-arrestin recruitment assay.…”
Section: Discussionmentioning
confidence: 99%
“…CBD has a low affinity for the CB1 receptor and functions as a noncompetitive allosteric antagonist. 23,38,39 When used at up to 5 lM, CBD fully inhibited the 2-LG re-sponse and substantially inhibited (*70%) the ACEA and AEA responses. However, its effect on 2-AG at this concentration was less pronounced, but others have also showed that it does not fully inhibit maximal 2-AG responses at this concentration in a similar b-arrestin recruitment assay.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, (−)-7-hydroxy-dimethylheptyl-CBD can inhibit both AEA uptake and degradation through fatty acid amide hydrolase (FAAH) activity [121]. Recently, (−)-dimethylheptyl-CBD has been shown to be a CB1 receptor agonist ( Table 2) in HEK-293A cells [122]. In addition, by reducing the expression of pro-inflammatory genes (IL-1b, IL-6, and TNF-α), it exhibits a dose-dependent anti-inflammatory effect on microglia BV-2 cells [30].…”
Section: Cb1/cb2 Receptorsmentioning
confidence: 99%
“…Table 2. Influence of natural and synthetic CBD derivatives on receptor activation (X: agonist activation or Y: antagonist activation by related CBD derivative; * weak affinity; #: full name is in chapter 4.1) [2,24,72,76,[114][115][116]120,[122][123][124][125][126][127]130]. Natural CB1 CB2 Gpr55 Gpr18 TRPV1 TRPA1 TRPM8 5-HT…”
Section: Trpv1 5-ht 1a and Adenosine A 2a Receptorsmentioning
confidence: 99%
“…In this sense, it is possible that the diverse effects of CBD over CB1-expressing, heterogeneous neuronal populations may lead to both undesirable and protective consequences. CBD can have opposed effects on CB1 receptors, given that it can act as an indirect agonist (De Petrocellis et al, 2011) and as a biased negative allosteric modulator (Tham et al, 2019). The complex pharmacology of this phytocannabinoid possess interesting properties for the management of different neuropsychiatric conditions but can also lead to some undesirable effects that are especially hard to predict (Brown and Winterstein, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Its main molecular effects within the central nervous system are comprehended by the agonism of 5-HT1A, TRPV1, G-protein receptor 55 (GPR55), peroxisome proliferator-activated gamma (PPARγ) receptors and the antagonism of adenosine reuptake (Turner et al, 2017). Despite initial controversy about its endocannabinoid targets (Zlebnik and Cheer, 2016), recent evidence also supports CBD as a negative 6 allosteric modulator of CB1 and CB2 receptors at physiologically relevant concentrations (Laprairie et al, 2015;Martínez-Pinilla et al, 2017;McPartland et al, 2015;Navarro et al, 2018;Tham et al, 2019). In addition, CBD reduces anandamide (AEA) metabolism by inhibiting fatty acid amid hydrolase (FAAH) enzymatic activity (De Petrocellis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%